Trade and Income in the Long Run : Are There Really Gains, and Are They Widely Shared? - Cerdeiro, Diego; Komaromi, Andras (Washington, D.C. : International Monetary Fund, 2017)
In the cross section of countries, there is a strong positive correlation between trade and income, and a negative relationship between trade and inequality. Does this reflect a causal relationship? We adopt the Frankel and Romer (1999) identification strategy, and exploit countries' exogenous geographic characteristics to estimate the causal effect of trade on income and inequality. Our cross-country estimates for trade's impact on real income are consistently positive and significant over time. At the same time, we do not find any statistical evidence that more trade increases aggregate measures of income inequality. Heeding previous concerns in the literature (e.g. Rodriguez and Rodrik, 2001; Rodrik, Subramanian and Trebbi, 2004), we carefully analyze the validity of our geography-based instrument, and confirm that the IV estimates for the impact of trade are not driven by other direct or indirect effects of geography through non-trade channels.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet